Effects of bioavailable phosphorus and soil biota on typical Nardus grassland species in competition with fast-growing plant species. (January 2021) - Schelfhout, Stephanie; Wasof, Safaa; Mertens, Jan; Vanhellemont, Margot; Demey, Andreas; Haegeman, Annelies; DeCock, Eva; Moeneclaey, Iris; Vangansbeke, Pieter; Viaene, Nicole; Baeyen, Steve; De Sutter, Nancy; et al.
Graphical abstract: Highlights: Biomass of oligotrophic indicator species dropped above 11.5 mg POlsen kg −1 . The experimental POlsen threshold is comparable to the threshold in remnant fields. Oligotrophic indicator species' relative biomass was high if total biomass was low. Oligotrophic indicator species persisted in phosphorus-poor mesocosms. Abstract: The restoration of Nardus grasslands is often hampered by high bioavailability of soil phosphorus and disturbed soil communities. In order to better understand these bottlenecks, we studied Nardus grassland species grown together in communities with fast-growing species in 50-liter pots along a gradient of bioavailable phosphorus with or without inoculated soil biota. These mesocosms allowed the plants to freely interact, including competition for light and nutrients. We investigated changes in the plant community composition along the phosphorus gradient using Threshold Indicator Taxa Analysis (TITAN). We found a negative threshold of 11.5 mg POlsen kg −1 with six significant indicator plant species. Above the threshold, a small increase in phosphorus resulted in a disproportionally large drop in biomass for the indicator species, including four typical Nardus grassland species. The decline in these 'oligotrophic indicator species' was also linked to increasing plant community biomass, so we suggest the oligotrophic indicator species to be outcompeted for light by fast-growing plant species. We did not find an effect of the soil biota treatment on the biomass of the oligotrophic indicator species, but did observe a positive effect of inoculation with soil biota on the total biomass of the plant community. Interestingly, the threshold for the plant communities in the mesocosm experiment was comparable to the upper bioavailable phosphorus concentrations in remnant Nardus grasslands in northern Belgium. For the restoration of Nardus grasslands, such phosphorus-poor soil conditions appear to be essential, because the plant species that typically occur in these grasslands are able to handle nutrient limitation, but not light limitation.